Czech Theatrical Market and Digital Film Piracy Economic Analysis and Suggested Policies - Janák, Pavel; Voráček, Jan; Vysoká škola ekonomická v Praze. Fakulta managementu; Haindl, Michal, 1955- (2014)
The Czech theatrical market faces a major digital piracy problem. The availability of illegitimate digital distribution channels represents a challenge for managers, especially when original movies are uploaded to the Internet before or during their theatrical release. The crucial managerial task is to solve the problems of losses caused by piracy, and to find a balance between antipiracy investment and the maximal benefits it brings. Therefore, to maximize stakeholder utility, management decision-making needs to be complemented and supported. Firstly, the research investigates the basis of digital piracy, discusses the effects it causes, focuses on relevant stakeholders. The thesis deals with knowledge management and system dynamics using its principles and approaches and proposes a model supporting strategic management decision-making. The created knowledge-based computational model simulates the market's development of the Czech theatrical industry related to digital film piracy in the following scenarios: current market settings, industry-based administration, government-based administration and a mixture of the last two; the results of the different scenarios are discussed, evaluated and compared. The findings indicate that with the current settings in the Czech theatrical industry, the losses caused by digital piracy keep increasing linearly. Industry-based administration implies that the losses level off with a negligible yearly increase and the government-based solution reduces the losses more than the industrial administration. Nevertheless, the results show minor differences in total box office revenues, while differences in antipiracy costs are vast. Therefore, the predictive experiment based on the current market environment represents the most efficient version of the experiments. Even though losses are, the highest, real box office revenues are only a little different
Simply put, a moderate increase in box office revenues paid for by massive investments into antipiracy seems inefficient.
Vedoucí práce: Jan Voráček
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2014
Obsahuje bibliografii
Rok obhajoby 2014
Keywords: management [obor disert. práce]; disertace; dissertations